HUBUNGAN ASUPAN MAKANAN (LEMAK, NATRIUM, MAGNESIUM) DAN GAYA HIDUP DENGAN TEKANAN DARAH PADA LANSIA DAERAH PESISIR (Studi di Wilayah Kerja Puskesmas Tegal Barat Kota Tegal) - Jatu Safitri Cahyahati; Apoina Kartini; M . Zen Rahfiludin (Jurnal Kesehatan Masyarakat (Undip), 2018)
Blood pressure is the power needed to pump the blood to flow through the blood vessels to meet nutritional needs and make it function optimally. High blood pressure mostly occurs in the elderly. There are several factors that influence the occurrence of high blood pressure, such as the intake of fat, sodium, magnesium, caffeine, and smoking behavior. This study aimed to analyze the correlation between food intake (fat, sodium, magnesium, caffeine) and smoking behavior with blood pressure in elderly who lived in the coastal areas in Puskesmas Tegal Barat, Tegal City. This study was an observational study with cross sectional study design. Samples were 60 elderly respondents who were selected based on purposive sampling. Data were collected by measuring blood pressure (Sphygmomanometer Aneroid), anthropometry, and FFQ-Semi Quantitative and analyzed with Rank Spearman test. The results showed that sodium intake (p = 0.001) was associated with systolic and diastolic blood pressure. While fat intake (p = 0.122) and (p = 0.165), magnesium (p = 0.173) and (p = 0.391), caffeine consumption (p = 0.913) and (p = 0.179), smoking behavior (p = 0.053) and (0.063) were not related to systolic and diastolic blood pressure. It could be concluded that high blood pressure is associated with sodium intake.